Understanding the Joint Impacts of Cognitive, Social, and Geographic Proximities on the Performance of Innovation Collaboration Between Knowledge-Intensive Business Services and the Manufacturing Industry: Empirical Evidence From China - Zhao, Ting; Yang, Meng; Cao, Zhijuan; Wang, Xiang (Frontiers in Psychology, 2022)
Most previous empirical studies just addressed the influence of geographical proximity on interactive learning regarding the collaboration between knowledge-intensive services (KIBS) and manufacturing industries. Drawing upon the social cognitive and knowledge-based perspective, this study bridged the research gaps by investigating the joint effects of geographical proximity and two representative non-geographic-proximities (i.e., cognitive proximity and social proximity) in fostering manufacturing firms’ innovation performance. In terms of the empirical analysis, we applied a research sample that involves data of various manufacturing industries in 260 cities of China from 2003-2014 to test the corresponding hypotheses. Additionally, Spatial Durbin Model (SDM) was adopted and the research findings showed that: (i) the geographic and social proximity significantly promote the knowledge transfer from KIBS to manufacturing firms, which further improves the innovation performance of the latter. However, the effect of cognitive proximity presents insignificant; (ii) the interactive effect of geographic and social proximity was positively associated the innovation collaboration between KIBS and manufacturing firms; (iii) although the individual effect of cognitive proximity was insignificant, when it interacted with geographic or social proximity, the joint effects were proved to promote the innovation performance of manufacturing firms. This study extends our understanding pertaining to the influencing mechanism of proximity for KIBS and innovation process. The findings proved that geographic and social proximity are two imperative facilitators of knowledge-creating collaboration, highlighting their indispensable role in moderating and mediating the knowledge transfer of KIBS as well as the innovation performance of manufacturing firms. Notably, cognitive proximity is contingent upon geographic and social proximity on its positive effects on the innovation performance for KIBS and their clients’ collaboration.